A bottom mounted wavemaker in water wave flumes. Issue 4 (4th July 2021) - Mahjouri, Saeed; Shabani, Rasoul; Badiei, Peyman; Rezazadeh, Ghader
Abstract : Reflections of the surface waves in hydraulic wave flumes could affect the performance of the common piston, hinged and plunger type wavemakers. This paper proposes a new wavemaker to produce surface waves where the possible reflections are barely able to affect its performance. The proposed wavemaker includes an oscillating paddle at the bottom of the flume where the produced upward flow induces travelling surface waves. An analytical study is carried out on the wave generation of the system. It is shown that the paddle length could significantly affect the height of the generated waves, which could not happen in conventional wavemakers. Effects of the water depth and the excitation frequency on the induced surface waves are also investigated. It is demonstrated that for a specific paddle length, water depth and forcing period the best performance of the system could be achieved.